PENGARUH EDUKASI MELALUI MEDIA E-POSTER TERHADAP PENGETAHUAN WANITA USIA SUBUR TENTANG ASI EKSKLUSIF (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Infant mortality rate (AKB) reflects the level of quality of life of the community. In 2020, AKB in Indonesia was 44,000 cases. in lowering AKB, one can be done by giving breast milk (breast milk) exclusively. Based on research conducted by Syafiq (2010) states that factors predisposing to failure of exclusive breastfeeding is less knowledge and experience of mothers. The coverage in Bandung kabupaten is 63.84%. Therefore, it is necessary to increase knowledge about exclusive breastfeeding through e-poster media. Objective: to know the effect of education through e-poster media on WUS knowledge about exclusive. Method: this study used a quasi experimental design with the design of one group pretest-posttest without control to a population of 2,210 and taken samples with the formula slovin then obtained the results of the sample as much as 96 WUS. Data collection was done by using closed question instruments, namely pretest media education e-poster and posttest . Data analysis using Wilcoxon test to prove research hypothesis. Results: the average knowledge of women of childbearing age (WUS) before being given education through e-poster media amounted to 79.38. The average knowledge of WUS after being given education through e-poster media is 96.88. Percentage increase in knowledge by 17.5. p value of (P=0.000). Conclusion: there is the effect of education through e-poster media on the knowledge of women of childbearing age about exclusive.